1994
DOI: 10.1021/ma00098a015
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of phase separation in mixtures of associating polymers and homopolymers in solution

Abstract: The phase behavior of mixtures of a hydrophobically modified polymer capable of forming associations and an unmodified polymer of the same chemical composition has been investigated. The associative thickener (AT) consists of polyethylene glycol) (PEG) end-capped at both ends with hydrophobic alkane groups. It is found that mixtures of the AT solution and the unmodified PEG phase separate into two distinct solutions, provided AT molar fractions are <0.65. This is despite the fact that the overall polymer conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 10 publications
7
40
0
Order By: Relevance
“…It is well known that the HEUR networks exhibit single viscoelastic relaxation. Due to this mechanical simplicity, the HEUR networks have been employed as a model system of the transient network [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the HEUR networks exhibit single viscoelastic relaxation. Due to this mechanical simplicity, the HEUR networks have been employed as a model system of the transient network [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been experimentally reported that the relaxation time depends both on the concentration and the molecular mass [1][2][3]7) . Tanaka and Edwards proposed the modified model considering the recombination of the chains, to describe the deviation of the experimental results from the prediction of the classical theory [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…These bonds need to be sufficiently strong to produce a reasonable degree of incompatibility, while still remaining reversible so as not to trap the structure and hinder the lateral movement of the chains [17]. In our previous work using both theoretical calculations and Brownian dynamics simulations [17,27] we had shown the possibility of both bulk and surface phase separation, resulting from the presence of such reversible bonds between one set of molecules but not the other, in systems consisting of a mixture of the two.…”
Section: Discussionmentioning
confidence: 99%
“…These serve to produce weak reversible bonds, driven by hydrophobic forces, between the modified molecules, but not the unmodified ones. As a result, it is observed that the mixed solution breaks up into two distinct phases, one rich in the associating molecules and the other in unmodified ones [27][28][29][30]. We also suspect that the possible surface phase separation reported for certain mixed protein films occurring at air-water interfaces [31][32][33][34][35] is also the result of a very similar mechanism.…”
Section: Introductionmentioning
confidence: 86%
“…Hydrophobically modified PEO can be obtained by different methods including various linkers used to connect the PEO chain with the hydrophobic segment. The syntheses of modified PEO with linkers such as ethers,4 esters,5, 6 urethanes7, 8 or diurethanes9, 10 were reported.…”
Section: Introductionmentioning
confidence: 99%